Pushing daisies. The complete second season [videorecording (DVD)] - Dale, Jim; Pace, Lee, 1979-; Friel, Anna, 1976-; McBride, Chi; Greene, Ellen; Kurtz, Swoosie; Chenoweth, Kristin (Warner Home Video, 2009)
Ned is a young man with a very special gift. As a boy, Ned discovered that he could return the dead briefly back to life with just one touch. Now a pie maker, Ned puts his ability to use, not only touching dead fruit and making it ripe with everlasting flavor, but working with a private investigator to crack murder cases by getting the dead to name their killers. But Ned's life is complicated when he brings his childhood sweetheart back to life and keeps her alive. Life would be perfect except if Ned ever touches her again, she'll go back to being dead, this time for good.